2010
DOI: 10.1002/jor.21102
|View full text |Cite
|
Sign up to set email alerts
|

Carboxy terminus of secreted phosphoprotein‐24 kDa (spp24) is essential for full inhibition of BMP‐2 activity

Abstract: Secreted phosphoprotein-24 kDa (spp24) is a bone morphogenetic protein (BMP)-binding protein isolated from bone. It exists in a number of size forms and is hypothesized to function as a BMP latency protein and/or a ''slow release'' mechanism for BMPs involved in bone turnover and repair. We have examined the hypothesis that proteolytic modification of the C-terminus of spp24 affects its BMP-2-binding properties and bioactivity in the BMP-2-stimulated ectopic bone forming bioassay. Three different size forms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 18 publications
(30 reference statements)
1
19
0
Order By: Relevance
“…We have engineered a number of protein and peptide products that, while they are thought to function by a single mechanism (BMP binding), operationally they have seemingly paradoxically opposite outcomes along a spectrum from enhancement of BMP activity ("slow release") to inhibition of BMP activity ("sequestration") [9]. Among these peptides, full length Spp24, when applied to a collagen sponge to which BMP-2 was subsequently applied, dramatically inhibited the activity of BMP-2 in models of ectopic bone formation [29] and spinal fusion [9].…”
Section: Discussionmentioning
confidence: 99%
“…We have engineered a number of protein and peptide products that, while they are thought to function by a single mechanism (BMP binding), operationally they have seemingly paradoxically opposite outcomes along a spectrum from enhancement of BMP activity ("slow release") to inhibition of BMP activity ("sequestration") [9]. Among these peptides, full length Spp24, when applied to a collagen sponge to which BMP-2 was subsequently applied, dramatically inhibited the activity of BMP-2 in models of ectopic bone formation [29] and spinal fusion [9].…”
Section: Discussionmentioning
confidence: 99%
“…Spp2 is a bone matrix protein that is produced primarily in the liver and delivered to other tissues for function, especially the bone (1,11,24). The function of this protein in the normal bone environment is not clearly delineated.…”
Section: Discussionmentioning
confidence: 98%
“…The candidate gene, Secreted phosphoprotein-2 (Spp2), also known as secreted phosphoprotein-24 kDa (Spp24), has not been studied in the context of cardiovascular physiology but has been studied in the context of skeletal physiology (9) and in normal bone growth and turnover (11,50,51). Spp2 is a bone matrix protein that is produced primarily in the liver and delivered to other tissues for function, especially the bone (1,11,24).…”
Section: Discussionmentioning
confidence: 99%
“…Spp24 can bind with BMP2 and inhibit its osteogenic activity (28,29). Several studies have indicated that spp24 could inhibit cancer cell proliferation and tumor growth (22,23).…”
Section: Discussionmentioning
confidence: 99%